Avaliação da geração de Hg(0) em reator anaeróbio de fluxo ascendente de ETE - Michilini, Larissa Meneghin (Universidade Federal de São Carlos, 2018)
Mercury is a metal of high mobility and toxicity in the environment. The understanding of different aspects about its biogeochemical cycle is of fundamental importance for the management of this global pollutant. Different biotic and abiotic processes are responsible for the transfer between phases, involving the aqueous environment and the atmosphere, causing contaminated aquatic environments and wastewater to also act as emitters and/or remitters of mercury. The current concern about this type of environmental contamination can be attested by the recent Minamata Convention, an agreement signed in 2013 by 140 countries, promulgated by Brazil on August 14, 2018 and which provides the reduction of global mercury emissions. This agreement is both the source control as use restrictions, and Brazil is one of the signatories. The aim of this study was to determine the total mercury (HgT) and Hg(0) in samples of raw sewage and effluent from the Upflow Anaerobic Sludge Blanket Reactor(UASB) of the wastewater treatment plant (ETE-Monjolinho) in the city of São Carlos-SP, using a cold vapor atomic fluorescence spectrometry (CVAFS), a strategy that allows the limits of detection less than ng L-1, which is low enough to allow quantification in any of the matrices of interest. The analyzes were performed between October 2017 and July 2018, in samples collected monthly. The mean concentrations for HgT in ng L-1 were 24.4 ± 9.7 for the station's affluent and 21.9 ± 9.3 for the anaerobic reactor effluent. The results showed that both HgT as well as Hg(0) in the affluent have a correlation with the pH, where in higher pH there is a higher formation of Hg (0) and consequently lower concentrations of HgT and in pH with lower values the tendency is to contain higher concentrations of HgT and lower formation of Hg(0). Correlations between HgT, Hg(0) and dissolved organic carbon (DOC) showed that in the effluent samples as the higher DOC concentration had higher concentration of HgT and lower concentration of Hg(0), supporting the hypothesis of the complexing capacity of organic matter (OM). In the affluent samples this trend was observed more subtly in the results. Regarding to Hg(0), the results obtained in the studied period show that both samples from the station's effluent and reactor effluent mostly immediately reduced the added Hg2+ in the samples, but it was noticed that with the passage of time this tendency has decreased. A reduction capacity of Hg(II) to Hg(0) was found in both the affluent and the reactor's effluent. In the presence of Hg2+ additions, a formation of Hg(0) in the affluent of the order of 29 to 2100 pg L-1 and in the effluent of the order of 23 to 570 pg L-1 was observed. A mass balance that takes into account the annual emission of the WWTP in terms of HgT, points to affluent values of 461 g and 414 g effluent, reaching a removal of 47 g year-1, a value that is partitioned between incorporation to the sludge and emission into the atmosphere after reduction.
Evaluation of the generation of Hg(0) in up flowanaerobic reactor of WWTP
Keywords: Ciclo biogeoquímico do mercúrio; Emissão de mercúrio; Fontes de mercúrio; Formação de Hg (0); Tratamento anaeróbio de esgotos; Biogeochemical cycle of mercury; Mercury emission; Mercury sources; Hg(0) Formation; Anaerobic wastewater treatment; CIENCIAS EXATAS E DA TERRA::QUIMICA; CIENCIAS EXATAS E DA TERRA::QUIMICA::QUIMICA ANALITICA